Impact of the COVID-19 pandemic on staff turnover at long-term care facilities: a qualitative study - Ram Gopal; Niam Yaraghi; Ola Henfridsson (BMJ Open)
Objective The objective of this research was to explore the lived experiences of long-term care facilities’ staff during the COVID-19 pandemic and examine if and how the pandemic played a role in their decision to leave their jobs.Design Qualitative study using thematic analysis of semistructured interviews. Interview transcripts were analysed using coding techniques based in grounded theory.Participants A total of 29 staff with various roles across 21 long-term care facilities in 12 states were interviewed.Results The pandemic influenced the staff’s decision to leave their jobs in five different ways, namely: (1) It significantly increased the workload; (2) Created more physical and emotional hazards for staff; (3) Constrained the facilities and their staff financially; (4) Deteriorated morale and job satisfaction among the staff and (5) Increased concerns with upper management’s commitment to both general and COVID-19-specific procedures.Conclusions Staff at long-term care facilities discussed a wide variety of reasons for their decision to quit their jobs during the pandemic. Our findings may inform efforts to reduce the rate of turnover in these facilities.